2020
DOI: 10.3390/w12071932
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Trends in 20-Day Cumulative Precipitation for Residential Rainwater Harvesting in Poland

Abstract: Rainwater harvesting (RWH) for domestic uses is widely regarded as an economic and ecological solution in water conservation and storm management programs. This paper aims at evaluating long-term trends in 20-day cumulative rainfall periods per year in Poland, for assessing its impact on the design and operation conditions for RWH systems and resource availability. The time-series employed corresponds to a set of 50-year long time-series of rainfall (from 1970 to 2019) recorded at 19 synoptic meteorolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 50 publications
(177 reference statements)
1
14
0
Order By: Relevance
“…It was observed that during the rainwater storage process, various microorganisms reflect specific temperature reactions, for example, longer persistence of E. coli was detected in rainwater at 4 • C, which is consistent with the data on the survival of pathogenic microorganisms [52].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It was observed that during the rainwater storage process, various microorganisms reflect specific temperature reactions, for example, longer persistence of E. coli was detected in rainwater at 4 • C, which is consistent with the data on the survival of pathogenic microorganisms [52].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the presented study seems to be justified also due to often implemented closed underground storage solutions according to the use of rainwater, for example, at newly designed estates of single-family houses (used for aesthetic and visual reasons and also due to limited space) [51,52]. The storage temperature of rainwater in underground containers is constant.…”
Section: Discussionmentioning
confidence: 92%
“…This is disadvantageous because, in Poland, the water resources are relatively low when compared to the European average. According to Canales et al [5], the Polish average water resources per capita equals 1600 m 3 while the European average (4800 m 3 ) is three times higher. Climate change and global warming affect the fresh water availability [6], hence the Polish water resources are constantly decreasing.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change and global warming affect the fresh water availability [6], hence the Polish water resources are constantly decreasing. With population growth and water usage, there is a risk that the country will have to face water shortages in the future [5]. Poland is located in a temperate climate in which rains are observed throughout the year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation